Single nucleotide polymorphisms in the TGF-β1 gene are associated with polycystic ovary syndrome susceptibility and characteristics: a study in Korean women - Roh, Eun Youn (J Assist Reprod Genet, 2016)
PURPOSE: Although many hypotheses regarding the pathogenesis of polycystic ovary syndrome (PCOS) have been generated, genetic studies have not identified specific genes that play a role in PCOS etiopathogenesis. This study aimed to investigate the relationship between TGF-β1 gene polymorphism and PCOS in Koreans. METHOD: A total of 51 Korean women with PCOS and 69 healthy women were enrolled. We analyzed 4 single nucleotide polymorphisms (SNPs) of the TGF-β1 gene (rs11466313, rs1800469, rs2317130, and rs4803457). We also analyzed laboratory measurements, such as free testosterone, glucose, and cholesterol. RESULTS: The frequencies of rs1800469T allele negativity, rs4803457T allele negativity, the rs1800469CC genotype, and the rs4803457CC genotype showed positive associations with PCOS (P = 0.003, P = 0.027, P = 0.009, and P=0.031, respectively), whereas the haplotypes rs1800469C–rs4803457T and rs1800469T–rs4803457T showed negative associations with PCOS. A strong protective effect of the “rs1800469CT–rs4803457TT” combination (OR = 0.09) and a strong risk effect of “rs1800469CC–rs4803457CC” (OR = 6.23) for PCOS were observed. The rs1800469C/T and rs2317130C/T SNPs exhibited associations with several laboratory measurements with various levels of significance. CONCLUSION: The results demonstrated an association of TGF-β1 gene polymorphisms with the development and/or characteristics of PCOS in the Korean population.